Research Ethics Committee decision-making in relation to an efficient neonatal trial - Gale,CRK; Hyde,MJH; Modi,N (Archives of Disease in Childhood-Fetal and Neonatal Edition, 2016)
ObjectiveRandomised controlled trials, a gold-standard approach to reduce uncertainties in clinical practice, are growing in cost and are often slow to recruit. We determined the acceptability to United Kingdom (UK) Research Ethics Committees (REC) of approaches to facilitate large, efficient clinical trials. DesignWe developed a protocol in collaboration with parents, for a comparative-effectiveness, randomised controlled trial comparing two widely used blood transfusion practices in preterm infants. We incorporated four approaches to improve recruitment and efficiency: i) point-of-care design using Electronic Patient Records for patient identification, randomisation and data acquisition, ii) short two-page information sheet; iii) explicit mention of possible inclusion benefit; iv) opt-out consent with enrollment as the default. With the support of the UK Health Research Authority, we submitted an identical protocol to 12 UK REC. SettingResearch Ethics Committees in the UKMain outcomeNumber of REC granting favourable opinions.ResultsThe use of Electronic Patient Records was acceptable to all REC; one REC raised concerns about the short parent information sheet, 10 about inclusion benefit and 9 about opt-out consent. Following responses to queries 9 REC granted a favourable final opinion; 3 rejected the application because they considered the opt-out consent process invalid. ConclusionsA majority of REC in this study consider the use of Electronic Patient Record data, short information sheets, opt-out consent and mention of possible inclusion benefit to be acceptable in neonatal comparative-effectiveness research. We identified a need for guidance for REC in relation to opt-out consent processes. These methods provide opportunity to facilitate large randomised controlled trials.